Heterogeneous Water Oxidation: Surface Activity versus Amorphization Activation in Cobalt Phosphate Catalysts - González Flores, Diego (2015)
Is water oxidation catalyzed at the surface or within the bulk volume of solid oxide materials? This question is addressed for cobalt phosphate catalysts deposited on inert electrodes, namely crystallites of pakhomovskyite (Co3(PO4)2⋅8 H2O, Pak) and phosphate‐containing Co oxide (CoCat). X‐ray spectroscopy reveals that oxidizing potentials transform the crystalline Pak slowly (5–8 h) but completely into the amorphous CoCat. Electrochemical analysis supports high‐TOF surface activity in Pak, whereas its amorphization results in dominating volume activity of the thereby formed CoCat material. In the directly electrodeposited CoCat, volume catalysis prevails, but not at very low levels of the amorphous material, implying high‐TOF catalysis at surface sites. A complete picture of heterogeneous water oxidation requires insight in catalysis at the electrolyte‐exposed “outer surface”, within a hydrated, amorphous volume phase, and modes and kinetics of restructuring upon operation.